2011
DOI: 10.1002/pros.21373
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression pathways of high grade localized prostate cancer

Abstract: In addition to androgen receptor signaling, growth factor, and cytokine mediated pathways are active in clinically localized high grade prostate cancer. The availability of therapeutics that selectively target these pathways encourages the development of clinical trials for their selective use in the neoadjuvant or adjuvant setting in men at high risk for disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 60 publications
7
75
1
Order By: Relevance
“…We applied Analysis of Functional Annotation (AFA), a gene set analysis approach, on differential gene expression data obtained from distinct comparisons and across different studies to identify biological processes and signaling pathways modulated by HDACis in PCa cells. 10,11,18,19,65 Overall, this methodology extends gene set analysis procedures, such as GSEA or parametric analysis of gene set enrichment (PAGE), by investigating biological processes enrichment over multiple experimental conditions as briefly summarized below. [12][13][14] FGS, recapitulating distinct and complementary biological concepts such as cellular signaling pathways, PPI networks, downstream transcriptional responses, gene expression regulatory networks orchestrated by transcription factors and microRNA targets, were retrieved in the form of gene lists from various publicly available databases (see Table S1 and http://luigimarchionni.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied Analysis of Functional Annotation (AFA), a gene set analysis approach, on differential gene expression data obtained from distinct comparisons and across different studies to identify biological processes and signaling pathways modulated by HDACis in PCa cells. 10,11,18,19,65 Overall, this methodology extends gene set analysis procedures, such as GSEA or parametric analysis of gene set enrichment (PAGE), by investigating biological processes enrichment over multiple experimental conditions as briefly summarized below. [12][13][14] FGS, recapitulating distinct and complementary biological concepts such as cellular signaling pathways, PPI networks, downstream transcriptional responses, gene expression regulatory networks orchestrated by transcription factors and microRNA targets, were retrieved in the form of gene lists from various publicly available databases (see Table S1 and http://luigimarchionni.…”
Section: Methodsmentioning
confidence: 99%
“…15 In the current study, we applied AFA, as previously described, to enable the interpretation of these results in the context of relevant cancer biology. 10,11,[18][19][20] To this end, we selected Functional Gene Sets (FGS) from distinct databases, recapitulating different and complementary biological concepts: (1) cellular signaling pathways from Pathway Commons, (2) PPI networks from the National Center for Biotechnology Information (NCBI) Entrez Gene database, (3) downstream transcriptional responses, and (4) gene expression regulatory networks orchestrated by transcription factors and microRNA targets. These collections included, among others, the Human Protein Reference Database (HPRD), GO, Kyoto Encyclopedia of Genes and Genomes (KEGG), the Molecular Signature Database (MSigDB), the Pathway Commons and NCBI Entrez Gene databases.…”
Section: Analysis Of Functional Annotation (Afa) After Treatment Withmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, SPARCL1 gene expression was not significantly lost in benign prostatic hyperplasia or PIN (Fig. S6 D and E) (27,28,37) (Oncomine). Interestingly, gene-profiling data from the same cohorts showed that RHOC gene expression did not correlate with prostate cancer grade (Fig.…”
Section: Sparcl1 Expression Inversely Correlates With Prostate Cancermentioning
confidence: 95%
“…Interestingly, gene-profiling data from the same cohorts showed that RHOC gene expression did not correlate with prostate cancer grade (Fig. S6 F and G) (27,28), suggesting that alterations in RHOC activity as opposed to expression levels, mediate RHOCinduced metastatic progression (38).…”
Section: Sparcl1 Expression Inversely Correlates With Prostate Cancermentioning
confidence: 98%